Pride and prejudice - Davidson, Susanna; Bursi, Simona Kelly, Alison Austen, Jane (Usborne Publishing Ltd. London, 2011)
The Bennett sisters are coming of age and it's time for them to find husbands if they want to find their place in high society. But will everything end up as they hope?